(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The use of current modified rules for intubation can result in better outcome with respect to preventing transmission of COVID-19 infection to healthcare providers. We aimed to assess the effect of implementing preventive and managerial protocols related to tracheal intubation of COVID-19 patients on preventing adverse clinical and psychological outcomes in personnel of intensive care units. Methods: This randomized single-blinded clinical trial study was performed on all personnel of ICU in a referral center for COVID-19 patients in Tehran in April 2020. The personnel were assigned into two group as the intervention group including personnel who received the necessary training to perform intubation based on existing standard and modified protocol and the control group that did not participate in the training sessions and continued their routine performance. Along with the clinical assessments, the personnel were assessed for depression and stress symptoms using the short form of Depression Anxiety and Stress Scale (DASS), 14 days after educational session. Results: There was no difference in clinical symptoms, hemodynamic condition, and laboratory findings across the two groups of personnel. The assessment of psychological aspects in both intervention and control group showed no difference in mean depression score as well as the severity of depressive mood, but the mean stress score in the two groups was 7.42±2.00 and 14.92±5.79 respectively indicating a significant difference (p = 0.007). In this regard, stress in any of its severity was not found in the personnel of education-based intervention group, however more than half of the personnel in control group suffered from mild to moderate stress. Conclusion: The scheduling and conducting training sessions and curricula related to intubation of COVID-19 patients can be very effective in reducing the level of personnel stress and therefore may reserve their occupational performance and minimized the likelihood of exposure to COVID-19.